ORGANIZATIONAL CHANGE STRATEGIES IN THE CURRENT ECONOMIC AND SOCIAL CONTEXT - Iuliana, TALMACIU (Strategii Manageriale)
The purpose of this paper is to analyze the main strategies for implementing organizational changes in the current social and economic context, characterized by an unprecedented dynamism. As a result, the paper presents the results of the research that have led to the identification of the factors determining the application of a particular strategy or even the usage of their mix. To achieve the established objectives set we have used as a research method the content analysis of various Romanian and foreign authors' work.